(untitled) (Research, Society and Development, 2018)
Sewage sludge is rich in organic matter and nutrients that can favor soil physico-chemical properties and crop development. However, the concentration of pathogenic microorganisms, trace elements and persistent organic pollutants are limiting factors for the application of this material to soil. This work aimed to verify the evolution of the publication of articles on the agricultural use of sewage sludge, between the years of 1980 and 2017. For this, a research of scientific articles indexed in the Web of Science database related to the subject was carried out found 1,166 articles. The results show that there has been a gradual increase in the number of publications between the decades. Among the countries that most published on the subject stand out the United States, Spain and Brazil. The articles dealing with the presence of pollutants showed that 35.5% had information about trace elements; 13.7% on pathogens; 15% on organic pollutants; while 27% approached nutrients, with emphasis on phosphorus, nitrogen and potassium. Regarding crops, the most mentioned were cereals, especially corn. From the analysis of data it was possible to observe the increase in the percentage of publications over the years on the subject, which suggests an increasing concern with the destination of the sludge, however, the presence of pollutants still represents a challenge for its use and should therefore be subjected to treatments to reduce its pollutant load and be used cautiously in accordance with the legislation.